SUPPRESSION OF APHANIZOMENON FLOS-AQUAE BY SOLID POLYMER ELECTRODE (SPE) MEMBRANE ELECTROLYSIS WITH AERATED SYSTEMS - Sardool, Gurminder; Daud, Mohmad Asari; Hamatani, Yoshiteru; Megat Mohd Noor, Megat Johari; Utsumi, Motoo; Goto, Masafumi; Sugiura, Norio; Ujang, Zaini (PERINTIS eJournal, 2021)
Algal blooms mainly heat-tolerant cyanobacteria pose a threat to drinking water quality not only in tropical regions but also during summer in temperate regions. The filamentous cyanobacteria are the most challenging to remediate as many technologies have reduced efficiencies in warm temperatures. Electrolysis, an advance oxidative technology (AOTs), shows high potentials in remediating persistent species. However, most electrolysis systems have been designed for highly polluted wastewaters. In this study, a solid polymer electrolysis (SPE) technology was tested for the suppression of freshwater cyanobacteria Aphanizomenon flos-aquae. The 4-day batch scale experiments revealed that electrolysis significantly suppressed Aphanizomenon successfully at 35°C without reduced efficiency compared to at 25°C. The evidence of suppression was indicated by (i) reduced cyanobacterial cell density, (ii) suppression rate constant (k) of - 0.1269 + 0.0805 day-1 at 35°C and -0.1486 + 0.0592 day-1 at 25°C, (iii) discolouration of media and (iv) reduction in filament length (p<0.05). Aerated systems instead significantly enhanced the proliferation of the filamentous cyanobacteria, evidenced by increased cell density, higher growth rate, more intense media colour and elongated filament lengths. Hence aeration is a less recommended technology for suppression of persistent heat-tolerant cyanobacteria while the SPE electrolysis effectively suppresses Aphanizomenon flos-aquae.